Optogenetics Applications for Treating Spinal Cord Injury - Aftab Ahmad (Asian Spine Journal, 2015)
Cases of spinal cord injury (SCI) are increasing all over the world; and in USA alone, there are 273,000 patients, which not only leads to morbidity and mortality but also results in a great economic burden. Many approaches are being used at the pre-clinical and clinical level to treat SCI including therapeutic agents, surgical decompression, stem cell therapy etc. Recently, a new approach called optogenetics has emerged in which light sensitive proteins are used to switch neurons on and off, and this approach has great potential to be used as therapy due to its specificity and rapid response in milliseconds. Few animal studies have been performed so far in which the respiratory and bladder function of rats was restored through the use of optogenetics. On the basis of promising results obtained, in the future, this approach can prove to be a valuable tool to treat patients with SCI.